Wertigkeit der MRT hinsichtlich TFCC-Läsionen außerhalb klinischer Studien = Quality Rating of MRI Regarding TFCC Lesions in the Clinical Practice - Hahn, Peter; Häusler, A.; Bruckner, Thomas; Unglaub, Frank (Handchirurgie, Mikrochirurgie, plastische Chirurgie, 2012)
Background: MRI diagnostic is used for wrist pain diagnostic frequently. Clinical studies in specialized centers show high sensitivity and speciﬁcity concerning TFCC lesions. The aim of this study is a comparison of MRI and arthroscopy regarding TFCC lesions not in a specialized but in a common medical environment. Patients/Material and Methods: We retrospectively recorded all patients between January 2004 and April 2012 who went through a wrist arthroscopy and had a preoperative MRI. 401 patients were identiﬁed, 218 males and 183 females. The average age was 42.4 (12-84) years. 88 examiners of radiological practices in the region of our hospital reported the MRI results used for this research. Results: In 334 cases TFCC lesions could be identiﬁed during arthroscopy. MRI showed an average sensitivity of 69 % and a speciﬁcity of 60 %. A Palmer classiﬁcation was reported through MRI in 58 cases. Most frequently, the MRI examiners reported a Palmer 1b lesion. That result could only be veriﬁed by arthroscopy in 11 cases. Conclusion: Although MRI has an acceptable degree of diagnostic test accuracy in controlled clinical studies, we do not recommend the general use of MRI in diagnosis of ulnocarpal wrist pain.